A confissão de Lúcio: o amor como alegorização do duplo - Oliveira, Lívia Mendonça de (2010)
Mário de Sá-Carneiro, portuguese author of the early twentieth century, published his main work, A confissão de Lúcio in 1914. Short poetic novel that is an allegory of the double in the myth of the androgynous as was conceptualized by Plato in The Symposium. Evoking the theme of the original androgyny, Mário de Sá-Carneiro intends to offer us an allegorical vision of Platonic myth of the androgynous, to say that each of us is originally double, although not split as Plato has proposed, but unaware of the other and the other part that also integrates us. Mário de Sá-Carneiro takes that thought to his narrative when he shows in Ricardo/Martha, the representation of the original androgynous of Plato, in Marta/Lúcio, as a metaphor of division; and, in Ricardo/Lúcio, the symbol of the meeting of the parts that reintegrates themselves only through erotic union. The love (Eros) appears here then, as an intermediate way of the allegorical replenishment. On these observations, in this work we have analyzed how Mário de Sá-Carneiro, in A confissão de Lúcio, deals with the concepts of love and eroticism, as allegorization of original union of love, the platonic love (Eros), through the three metaphors of primordial androgyny: Ricardo/Martha, Lúcio/Marta and, consequently, Ricardo/Lúcio